Functional and metabolic imaging in transthoracic biopsies guided by computed tomography. - Zurstrassen, Charles E.; Tyng, Chiang J.; Guimarães, Marcos D.; Barbosa, Paula N. V. P.; Pinto, Clovis A. L.; Bitencourt, Almir G. V.; Gross, Jeffersson L.; Lima, Eduardo N. P.; Cavalcante, Aline C. B. S.; Matushita Junior, João P. K.; Chojniak, Rubens (European Radiology, 2020)
Objectives: CT-guided biopsy of indeterminate lung lesions sometimes provides insufficient histological results due to tumor necrosis. Functional and metabolic methods such as DWI-MR and PET-CT may help by directing sample collection to a lesion area of greater biological representativeness. The objective is to evaluate the histopathological results based on findings on ADC and SUV levels in lung lesions suspected for primary cancer.Methods: Tissue samples were evaluated after undergoing biopsies guided by either DWI-MR or PET-CT findings. In each patient, sample collection from two lesion areas was guided by local ADC and SUV. Values were used to define areas of low vs. high suspicion for cancer.Results: Patients who underwent DWI-MR had median lesion size of 78.0 mm. Areas of higher suspicion (HSA) had a median ADC of 1.1 × 10-3 mm2/s, while areas of lower suspicion (LSA) had median ADC of 1.8 × 10-3 mm2/s (p = 0.0001). All HSA samples and 71.43% of LSA samples were positive for cancer (p = 0.0184). Patients who performed PET-CT had median lesion size of 61.0 mm. Median SUV was 7.1 for HSA and 3.9 for LSA (p = 0.0002). Positivity for cancer was observed in 76.9% of samples for both HSA and LSA (p = 0.0522).Conclusion: Use of DWI-MR and PET-CT showed that tumors are functional and metabolically heterogeneous and that this heterogeneity has implications for histopathological diagnosis.Key Points: • Lung cancer is heterogeneous regarding functional and metabolic imaging. • Tumor heterogeneity may have implications in histopathological diagnosis. • Intralesional lower levels of ADC target highly suspected areas with a significant improvement in lung cancer diagnosis.